Design Considerations for 3D Printed, Soft, Multimaterial Resistive Sensors for Soft Robotics - Shih, Benjamin; Christianson, Caleb; Gillespie, Kyle; Lee, Sebastian; Mayeda, Jason; Huo, Zhaoyuan; Tolley, Michael T. (Frontiers in Robotics and AI, 2019)
Sensor design for soft robots is a challenging problem because of the wide range of design parameters (e.g. geometry, material, actuation type, etc.) critical to their function. While conventional rigid sensors work effectively for soft robotics in specific situations, sensors that are directly integrated into the bodies of soft robots could help improve both their exteroceptive and interoceptive capabilities. To address this challenge, we designed sensors that can be co-fabricated with soft robot bodies using commercial 3D printers, without additional modification. We describe an approach to the design and fabrication of compliant, resistive soft sensors using a Connex3 Objet350 multimaterial printer and investigated an analytical comparison to sensors of similar geometries. The sensors consist of layers of commercial photopolymers with varying conductivities. We characterized the conductivity of TangoPlus, TangoBlackPlus, VeroClear, and Support705 materials under various conditions and demonstrate applications in which we can take advantage of these embedded sensors.